2015
DOI: 10.1007/s00253-015-6901-x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium resistance mechanism in Escherichia coli P4 and its potential use to bioremediate environmental cadmium

Abstract: A cadmium-resistant bacterium was isolated from industrial wastewater and identified as Escherichia coli (dubbed as P4) on the basis of morphological, biochemical tests and 16S rRNA ribotyping. It showed optimum growth at 30 °C and pH 7. E. coli P4 found to resist Cd(+2) (10.6 mM) as well as Zn(+2) (4.4 mM), Pb(+2) (17 mM), Cu(+2) (3.5 mM), Cr(+6) (4.4 mM), As(+2) (10.6 mM), and Hg(+2) (0.53 mM). It could remove 18.8, 37, and 56 % Cd(+2) from aqueous medium after 48, 96, and 144 h, respectively. Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…The intensity of the bands varied in different regions after the interaction with Cd 2+ . These results are similar to the findings by Khan [23]. SEM results revealed that P. shigelloides H5 adapts to high concentrations of cadmium ions in the environment by increasing the volume, which is similar to findings by Wu and Sun [22].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The intensity of the bands varied in different regions after the interaction with Cd 2+ . These results are similar to the findings by Khan [23]. SEM results revealed that P. shigelloides H5 adapts to high concentrations of cadmium ions in the environment by increasing the volume, which is similar to findings by Wu and Sun [22].…”
Section: Discussionsupporting
confidence: 82%
“…Many indigenous species of microorganisms have the capacity to tolerate heavy metals, for example, Enterococcus faecalis, Escherichia coli, Bosea sp., and Bacillus catenulatus [12,[20][21][22][23]. However, mutations can occur in some microorganisms due to the contamination of heavy metals in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biosorption of heavy metals using materials of microbial or plant origin has been considered as an innovative technology for removal of such pollutants [44]. For example, E. coli is biosorptive and has recently been used to adsorb heavy metals [45,46]. Enhanced uptake and bioaccumulation of mercury by E. coli have been achieved through genetic engineering to produce a recombinant strain [47].…”
Section: Metal Tolerance and Ion Accumulation In E Coli To Assess Tmentioning
confidence: 99%
“…The most prominent mechanism of resistance to Cd 2+ is the use of efflux pumps [17]. Several bacteria, such as Alcaligenes eutriphus [18], Staphylococcus aureus [19], Bacillus subtilis [20], Listeria monocytogenes [21] and Escherichia coli [22] have demonstrated resistance to Cd 2+ .…”
Section: Introductionmentioning
confidence: 99%